Women’s handwriting in the history of Azerbaijani literature (Philology, 2023)
The article examines the history of the development of women’s creativity in Azerbaijani literature. The stages of the historical development of women’s writing are traced against the background of general historical processes. The features of the development of socio-political life of Azerbaijan at different historical stages are especially emphasized and the influence of these processes on the development of women’s creativity in general is considered. The achievements of Azerbaijan in the East and in world civilization are listed. The work of such poets as Mehseti Ganjavi, Agabeim aga Javanshir, Khurshudbanu Natavan, Ashug Peri, Khairan Khanum is analyzed. Using specific literary samples from the works of poets, thematic and stylistic features of women’s writing are revealed. Some biographical data of poetesses that influenced the development of their creativity are also noted.The importance of the activities of Azerbaijani educators, who influenced the solution of the women’s issue and the formation of women‘s creativity, is also noted.As a result of the study, we can come to the conclusion that thanks to the activities and creativity of the above-mentioned poetesses, women‘s creativity found further development in Azerbaijani literature at further stages.
Keywords: Women’s creativity; history; literature; poetess